Bioinspired architectures toward improving damage resistance on CFRP laminates - Amorim, Luís Manuel Machado (2019)
Carbon fibre reinforced polymers (CFRP) are widely used in advanced applications due to their high performance and low weight, however, under certain conditions, they tend to develop internal damages that may compromise the component performance in service. Low velocity impact (LVI) events are one of the most common and dangerous solicitations that CFRP laminates must face during their life time, under these conditions they tend to develop so-called barely visible impact damages (BVID) that may propagate in service. To improve damage tolerance to LVI events, three new bioinspired CFRP laminates were developed and their mechanical properties and impact behaviour were compared to a typical aeronautic standard laminate in this work. All these studied laminates, having approximately the same thickness of 4 mm, were produced by vacuum bag infusion and observed under scanning electron microscopes (SEM) for assessing their processing quality. Tensile, interlaminar shear strength (ILSS) and LVI tests were performed in order to evaluate their Young’s modules, global delamination resistance and impact response. LVI tests were performed for all laminates at the four different impact energy levels of 13.5, 25, 40 and 80 J and damage shape and areas were subsequentially evaluated by ultrasonic C-scan. SEM observations and the good agreement between theoretical and experimental Young’s modules results demonstrated a processing quality. ILSS results have shown that the bioinspired hybrid laminate (HYB) presented better global resistance to delamination when compared to the other laminates. LVI tests and C-scan inspection have also demonstrated that HL and HL_S laminates exhibited higher resistance to damage propagation and smaller damaged area, respectively.